QUR’ANIC LITERACY THROUGH TADABBUR AL-QUR’AN COMIC - Ismail, Hidayatullah; Fatah, Nasrul; Salman, Salman; Saleh, Muhammad Hafiz (TAJDID: Jurnal Ilmu Ushuluddin, 2025)
Qur'anic literacy is something that is important in an effort to function the Qur'an as a guide for a Muslim's life. Qur'anic literacy is closely related to one's interaction with the Qur'an, whether it is reading, understanding, practicing and preaching it. Data shows that the level of Qur'anic literacy in Indonesia is quite good, but the data is only limited to the level of reading ability. So this study aims to elaborate a segment of higher Qur'anic literacy, namely at the level of understanding and appreciation, especially in children through the media of Qur'anic tadabbur comics. This research is a literature study using a qualitative approach and content analysis. The results of this study reveal that the Qur'an tadabbur comic provides a different color to the Qur'an literacy efforts for children. Where the cultivation of moral values, faith, and thick with the approach of scientific knowledge to children based on the value of the Qur'an is packaged interestingly.